MODEL PREDATOR DAN PREY DENGAN MODEL SUSCEPTIBLE - INFECTED – SUSCEPTIBLE - HIDAYATI, FIRSTY Nur; SUNARSIH, SUNARSIH (MATEMATIKA, 2010)
Â A predator-prey model with infected prey is an interaction between a predator and a prey population with infected prey. This model is a result of the predator-prey model with logistic growth in the prey population which is combined with Susceptible-Infected-Susceptible (SIS) model in the prey. The equations in this model are non linear differential equation with three dependent variables. In this system, is size of prey population at time , is the fraction of the prey that are infectious at time and is size of predator population at time . It is assumed that infected prey are vulnerable than by a factor . Stability analysis system is done to all five equilibriain this linearized. Each of stability in those equilibria points is based on theeigen values. Â